PENGARUH AKSES KREDIT PERBANKAN DAN PENGGUNAAN TEKNOLOGI FINANSIAL TERHADAP PEMBERDAYAAN EKONOMI LOKAL DI PROVINSI BALI - I Gusti Made Surya Baskara Bagiana; Pratiwi, I Gusti Ayu Made Agung Mas Andriani; Putra, I Komang Trisna Eka (Universitas Tabanan, 2025)
Local economic empowerment in Bali faces significant challenges, particularly concerning banking credit access and the utilization of financial technology (fintech). This study aims to explore the impact of these two factors on the development of Micro, Small, and Medium Enterprises (MSMEs). The methodology employed is a literature review, encompassing insights from various relevant sources such as articles, books, and online information. The findings indicate that although the distribution of People’s Business Credit (KUR) continues to rise, the dominance of the consumptive sector in credit distribution highlights the need for diversification for more sustainable growth. Fintech serves as a crucial tool in enhancing financial access for MSMEs, enabling them to apply for loans more easily and quickly. Case studies demonstrate how fintech, particularly online lending platforms, can boost the production and marketing of MSMEs. However, challenges such as gaps in digital financial literacy and consumer protection issues must be addressed. This research recommends the need for more focused policies to enhance financial literacy, simplify credit access, and strengthen regulations related to fintech. With these measures, it is anticipated that local economic empowerment in Bali can be effectively achieved, creating a more prosperous and competitive society in the digital era.